Short-term results of gait analysis with the Heidelberg foot measurement method and functional outcome after operative treatment of ankle fractures - Böpple, Jessica C.; Tanner, Michael Christopher; Campos, Sarah; Fischer, Christian; Müller, Sebastian; Wolf, Sebastian Immanuel; Doll, Julian (Journal of foot and ankle research, 2022)
Ankle fractures are common fractures in trauma surgery. Several studies have compared gait patterns between affected patients and control groups. However, no one used the Heidelberg Foot Measurement Method in combination with statistical parametric mapping of the entire gait cycle in this patient cohort. We sought to identify possible mobility deficits in the tibio-talar joint and medial arch in patients after ankle fractures as a sign of stiffness and pain that could result in a pathological gait pattern. We focused on the tibio-talar flexion as it is the main movement in the tibio-talar joint. Moreover, we examined the healing progress over time.